Asymptomatic Infant With Atypical SCID and Novel Hypomorphic RAG Variant Identified by Newborn Screening: A Diagnostic and Treatment Dilemma - Chitty-Lopez, Maria; Westermann-Clark, Emma; Dawson, Irina; Ujhazi, Boglarka; Csomos, Krisztian; Dobbs, Kerry; Le, Khuong; Yamazaki, Yasuhiro; Sadighi Akha, Amir A.; Chellapandian, Deepak; Oshrine, Ben; Notarangelo, Luigi D.; et al. (Frontiers in Immunology, 2020)
The T-cell receptor excision circle (TREC) assay detects T-cell lymphopenia (TCL) in newborns and is especially important to identify severe combined immunodeficiency (SCID). A spectrum of SCID variants and non-SCID conditions that present with TCL are being discovered with increasing frequency by newborn screening (NBS). Recombination-activating gene (RAG) deficiency is one the most common causes of classical and atypical SCID and other conditions with immune dysregulation. We present the case of an asymptomatic male with undetectable TRECs on NBS at 1 week of age. The asymptomatic newborn was found to have severe TCL, but normal B cell quantities and lymphocyte proliferation upon mitogen stimulation. Next generation sequencing revealed compound heterozygous hypomorphic RAG variants, one of which was novel. The moderately decreased recombinase activity of the RAG variants (16 and 40%) resulted in abnormal T and B-cell receptor repertoires, decreased fraction of CD3+ TCRVα7.2+ T cells and an immune phenotype consistent with the RAG hypomorphic variants. The patient underwent successful treatment with hematopoietic stem cell transplantation (HSCT) at 5 months of age. This case illustrates how after identification of a novel RAG variant, in vitro studies are important to confirm the pathogenicity of the variant. This confirmation allows the clinician to expedite definitive treatment with HSCT in an asymptomatic phase, mitigating the risk of serious infectious and non-infectious complications.